Application of Cognitive Deixis Theory in Persian Poetry Analysis as a Reference-Based Analysis (Case Study: a sonnet by Saadi) - Reza Refaee Ghaidimi Mashhad; Gholamhosein Gholamhoseinzade (مطالعات زبانی و بلاغی)
Cognitive deixis theory is one of the important issues in cognitive linguistics as determinants of the method of reference in the textual context. The aim of the present study is to investigate the application of the theory of cognitive deixis in the analysis of Persian poetry. The main claim made in the present study is that cognitive deixis is suitable tools for applying new methods in Persian poetry analysis that specifically analyze poetry based on types of references. In order to prove this claim and to study the application of this theory, first, the theoretical foundations of cognitive deixis and its basic issues such as the theory of deictic shift have been discussed and then a sonnet by Saadi has been studied and analyzed. The results of the present study show that cognitive deixis and the theory of deictic shift can cover the gap that exists in traditional rhetoric under the category of reference, and by applying these theories, we can design a kind of reference-based analysis in Persian poetry.